[Image 22] - Smith, Captain Sir William [?ob. 1732] (My University, 1812)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
Sketch of Naval Signal Station and defensible guard houses at Fannat Point seen as looking the way of Malin Hill, the station erected by Sir Wm Smith in 1804. The sketch made in 1812 by Sir Wm Smith.
Keywords: Malin Hill; Fannat Point; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1810-1820